A Shunt Active Power Filter with Enhanced Dynamic performance using Dual-Repetitive Controller and Predictive Compensation - Zhenfeng Xiao; Yilong Chen; Xiangtian Deng (International Journal of Power Electronics and Drive Systems (IJPEDS), 2013)
In this paper, the configuration characteristic of shunt active power filter (APF) with split capacitor is analyzed, as well as its principle diagram and control module. In order to improve the dynamic performance of a control system and to eliminate multi-repetitive errors (MRE), a combination strategy based on dual-repetitive controller (DRC) and PI controller is presented. One repetitive controller is for ensuring the current tracking accuracy and the other one is for enhancing dynamic response. And for purpose of eliminating the system delay brought by the inverter and special control, an improved predictive compensation method is proposed by using the pre-compensated angel. Using this composite control strategy to carry on industrial prototype simulation and field test, the experimental result shows that system compensation could effectively reduce the total harmonic distortion (THD) values from 26.02%, 26.94% and 26.27% to 4.20%, 4.59% and 4.35% for each phase of the current. And the full response time are all less than 10ms, fully meeting the standard of IEEE-519.DOI: http://dx.doi.org/10.11591/ijpeds.v3i2.2930